Україна в системі експорту відходів - Берлінг, Р. З. (Видавництво Національного університету «Львівська політехніка», 2001)
Відходи, що нагромадились на території України, сьогодні наносять значний економічний та екологічний збиток. Одним із можливих варіантів мінімізації негативної дії відходів передбачається їх продаж за кордон, де вони можуть бути використані в виробничому циклі, а отримані кошти, скеровані на управління відходами на Україні. Waste, which were accumulated on territory of Ukraine, on the given time they make a significant problem for those territories on which are stored putting them the significant economic and ecological loss. One of optional versions of minimization of negative action of a wastage supposes their sale abroad, where they can be utilised in a production cycle, and means, which will be received(obtained) to this to use on realization of the programs of management of a wastage on Ukraine.